The number of production wells affects the heat extraction performance of an enhanced geothermal system: insights from engineering-scale 3D THM coupling numerical simulations - Wang, Ziwei; Zhang, Bo; Yin, Likun; Yang, Liming; Fan, Yifan; Yin, Hongmei; Zhao, Peng; Liu, Jun (Frontiers in earth science (Lausanne), 2023)
Enhanced geothermal systems (EGSs) are expected to be one of the most promising methods of supplying energy to meet the world’s increasing energy demand. However, little attention has been paid to the influence of the number of production wells on the heat extraction performance of an EGS. A series of numerical simulations is organized in this work with three cases: Case 1 (one production well), Case 2 (two production wells), and Case 3 (three production wells). The results indicate that a slight temperature difference exists among the three simulation cases at the planes X-Y (Z = 0) and Y-Z (X = 0), while Case 1 ensures a greater cooling area, and the more production wells, the smaller the cooling area during the heat extraction in plane X-Z (Y = 0). In addition, the continuous injection of cooling water from the injection well and its arrival at different reference points enable the temperature at each point to declining with a variable amplitude of variation. This work also sets an efficiency ( ef ) to investigate the temperature variation in the EGS, where Case 1 exhibits a similar variation as Case 2, which is also similar to Case 3. It is hoped that this work will play a guiding role in EGS-related exploration and exploitation.